2015
DOI: 10.30552/ejihpe.v4i3.75
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida de los mayores que viven institucionalizados en residencias para mayores: Un análisis cuantitativo

Abstract: Las residencias para mayores parecen "instituciones cerradas" o "microcosmos independientes" centrando el interés de los medios de comunicación sólo en las deficiencias de las residencias para mayores. Objetivos: comparar la calidad de vida, capacidad funcional, el grado dependencia y los síntomas depresivos de las personas mayores institucionalizadas en residencias comparándolas con los mayores que residen junto a sus familiares. Material y método: se han analizado la calidad de vida y las alteraciones física… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the period considered, studies have been found that focus on obtaining relationships between factors associated with QoL, as well as predictors of QoL of residents. Among the studies that relate factors associated with QoL we can differentiate three subgroups (Table 6): on the one hand, those that establish dimensions related to different factors (Acevedo Alcaraz, 2015;Acevedo Alcaraz, 2016;Cuadros Bordal, 2013;Garrido-Abejar et al, 2012;Huesa Andrade, 2020;Lluesma-Vidal et al, 2021;Luque-Reca et al, 2015;Martín Aranda, 2019;Rodríguez-Blazquez et al, 2012;Sarabia Cobo, 2014); those using general QoL measurement instruments applied to NHs (Del Rocío Santana-Berlanga et al, 2020;Lucas-Carrasco et al, 2011;Perez-Ros & Martínez-Arnau, 2020); and finally those dealing with NH culture change or aspects that could influence it (Flecha García, 2019;González Casas et al, 2020;Rojano i Luque et al, 2021). The integration of the identified dimensions, together with those already established, allows a better definition of the QoL construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the period considered, studies have been found that focus on obtaining relationships between factors associated with QoL, as well as predictors of QoL of residents. Among the studies that relate factors associated with QoL we can differentiate three subgroups (Table 6): on the one hand, those that establish dimensions related to different factors (Acevedo Alcaraz, 2015;Acevedo Alcaraz, 2016;Cuadros Bordal, 2013;Garrido-Abejar et al, 2012;Huesa Andrade, 2020;Lluesma-Vidal et al, 2021;Luque-Reca et al, 2015;Martín Aranda, 2019;Rodríguez-Blazquez et al, 2012;Sarabia Cobo, 2014); those using general QoL measurement instruments applied to NHs (Del Rocío Santana-Berlanga et al, 2020;Lucas-Carrasco et al, 2011;Perez-Ros & Martínez-Arnau, 2020); and finally those dealing with NH culture change or aspects that could influence it (Flecha García, 2019;González Casas et al, 2020;Rojano i Luque et al, 2021). The integration of the identified dimensions, together with those already established, allows a better definition of the QoL construct.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize the importance of enhancing the autonomy of older adults, both at the residential level and at home (Huesa Andrade, 2020). In general, older adults who reside with their relatives or in their own homes tend to manifest worse QoL conditions in different dimensions (self-acceptance, relationships, autonomy, mastery of the environment, personal growth, purpose of life,...) (Acevedo Alcaraz, 2015;Cuadros Bordal, 2013;Sarabia Cobo, 2014). Thus, the current model of residences requires a change, allowing a real response to the needs of institutionalized older adults (Acevedo Alcaraz, 2015), taking into account that the dependence of older adults is a complex phenomenon, which demands different types of intervention, including common support actions that tend to cover the absence of autonomy in daily life, without resorting to institutionalization (Sarabia Cobo, 2014).…”
Section: Referencementioning
confidence: 99%